2017
DOI: 10.1039/c7dt01899a
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene-fused phospholes

Abstract: A calix [4]arene-based biarylphosphine has been synthesised and catalytically converted into two diastereomeric, calixarene-fused phospholes. arene has been prepared and its coordinative properties investigated. When heated in the presence of palladium, the new biarylphosphine undergoes conversion into two diasteromeric, calixarene-fused phospholes. In both, the P lone pair adopts a fixed orientation with respect to the calixarene core. The more hindered phosphole (8), i.e. the one with the endo-oriented lone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…In both tests, a high proportion of branched aldehyde was obtained, and no hydrogenated products were detected. The conventional selectivities observed were not unusual for Rh/P(III)‐systems, for example PPh 3 leads to 94 % of branched aldehyde . It was suggested that, during the catalysis, the phenyl substituent is kept away from the calixarenyl cavity, especially when ligand bearing bulky t Bu groups ( 1 ) was employed.…”
Section: Rhodium‐catalyzed Styrene Hydroformylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In both tests, a high proportion of branched aldehyde was obtained, and no hydrogenated products were detected. The conventional selectivities observed were not unusual for Rh/P(III)‐systems, for example PPh 3 leads to 94 % of branched aldehyde . It was suggested that, during the catalysis, the phenyl substituent is kept away from the calixarenyl cavity, especially when ligand bearing bulky t Bu groups ( 1 ) was employed.…”
Section: Rhodium‐catalyzed Styrene Hydroformylationmentioning
confidence: 99%
“…The calix[4]arene‐fused benzophosphole 11 (Figure ), prepared according Chatani's method, was studied by Elaieb et al The latter synthesis was not stereoselective, indeed, the crude mixture afford two pairs of diastereomeric calixarenyl benzophospholes having their phosphorus lone electron pairs endo ‐ or exo ‐oriented with respect to the cavity. Nevertheless, the diastereomers could be separated by column chromatography to isolate compound 11 in 60 % yield as a racemic mixture of two enantiomers, ( P , R )‐ 11 and ( M , S )‐ 11 , where the phosphorus lone pairs are endo ‐oriented.…”
Section: Rhodium‐catalyzed Styrene Hydroformylationmentioning
confidence: 99%
“…Similarly, Mattay has employed an intramolecular palladium catalysed cyclisation, but the desired racemic ICC product diastereomer 54 is complicated to remove from the non‐ICC C s ‐diastereomer (not shown; formed in a 1:1 ratio), making the overall yield low . Finally, Sémeril and Matt have very recently reported a calix[4]arene phosphole 56 which may also offer interesting applications if the enantiomers can be separated …”
Section: Meta‐functionalisationmentioning
confidence: 99%
“…[73] Finally,S Ømeril and Matt have very recently reported ac alix [4]arene phosphole 56 which may also offer interesting applicationsifthe enantiomerscan be separated. [74]…”
Section: Meta-functionalisationmentioning
confidence: 99%
“…Our own interest has been in the synthesis of inherently chiral calix[4]arenes whose chiral nature is a result of selective substitution on the calix[4]arene by various functional groups [9]. In particular, we have focused on the less-studied meta -substituted derivatives [10] whose inherent chirality is more commonly introduced by a suitable directing group [1115] (see Fig. 1), although two unusual methods have also been reported [1617].…”
Section: Introductionmentioning
confidence: 99%